Potensi Dan Uji Stabilitas Ekstrak Lawsonia Inermis Sebagai Cat Penutup Pada Gram Staining Dengan Variasi Suhu: Potency and Stability Test of Lawsonia inermis Extract as Counterstain on Gram Staining with Temperature Variation - Asfiya, Nida Azki; Novalina, Dhiah; Astuti, Tri Dyah (Borneo Journal of Medical Laboratory Technology, 2024)
Gram staining is one of the methods used for bacterial identification. Safranin is one of the dye substances employed in Gram staining. The toxicity and health hazards associated with the use of safranin have been extensively reported, especially the risk of contamination from synthetic dye waste. The use of synthetic dyes is highly hazardous as it can lead to cancer, kidney, and liver damage. A potential alternative for Gram staining is the use of henna leaves (Lawsonia inermis), which contain the dye substance lawsone. However, natural dyes are susceptible to temperature changes.This research aims to determine the ability of henna leaves to stain bacteria as a counterstain in Gram staining and to assess the temperature stability of the henna leaf extract under various temperature variations. This study is a qualitative descriptive research with an experimental design conducted in the Microbiology Laboratory of the Faculty of Health Sciences at 'Aisyiyah University Yogyakarta. The results of Gram staining for Gram-negative bacteria (Escherichia coli) at temperatures of 40°C and 80°C show no contrast with the background, while Gram-positive staining for Staphylococcus aureus appears contrasting against the background. It can be concluded that the Gram staining of Escherichia coli bacteria with Lawsonia inermis extract at temperatures of 40°C and 80°C yields staining results that lack contrast between bacterial cells and the background. In contrast, Staphylococcus aureus bacteria exhibit contrasting staining results between bacterial cells and the background. The stability test of Lawsonia inermis extract indicates greater stability at 40°C compared to 80°C